The Ecosystem of Metaverse and AI-Based Economic Learning: A Literature Review on 21st Century Education Innovations - Fatulloh, M. Amin; Judijanto, Loso; Tohir, Ahmad; Prananda, Gingga; Lestari, Nana Citrawati (The Future of Education Journal, 2025)
This study aims to explore the application of metaverse technology and artificial intelligence (AI) in economic learning in the 21st century, focusing on their impact on students' learning experience and comprehension. The method used in this research is a literature review with a descriptive qualitative approach, analyzing various previous studies related to the use of these technologies in economic education. The findings indicate that the metaverse can enhance interactivity and provide realistic economic simulations, while AI enables more personalized learning tailored to students' abilities and needs. However, challenges include limited digital infrastructure and a lack of preparedness among educators in adopting this technology. The conclusion of this study emphasizes the importance of improving infrastructure, providing educator training, and adjusting curricula to maximize the potential of technology in economic education, in order to create more effective learning that is relevant to the needs of the 21st century.